2002
DOI: 10.1038/modpathol.3880574
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Cytokeratins 7 and 20 Does Not Differentiate between Barrett's Esophagus and Gastric Cardiac Intestinal Metaplasia

Abstract: Long segment Barrett's esophagus (LSBE) is a recognized risk factor for the development of esophageal dysplasia and carcinoma. However, the risk of dysplasia arising within intestinal metaplasia below a normal-appearing Z-line (i.e., in native cardiac mucosa) is unknown. Regular endoscopic surveillance is required in patients with LSBE and is frequently performed in short segment BE (SSBE), but the need for surveillance in cardiac intestinal metaplasia (CIM) is unknown. Unfortunately IM arising in SSBE and imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 29 publications
3
40
0
1
Order By: Relevance
“…These results are similar to some previous reports (5,25), but were not always reproducible. The apparent discrepancy between studies may be due to a number of factors, including inaccurate visualization of short segment BE on endoscopy, interobserver variability, tissue fixation differences, and immunohistochemical staining differences (eg, antigen retrieval methods (25). Another important factor is the anatomical location from which the biopsy was taken, because biopsies obtained distal to the cardia have a significantly lower likelihood of showing a BE pattern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are similar to some previous reports (5,25), but were not always reproducible. The apparent discrepancy between studies may be due to a number of factors, including inaccurate visualization of short segment BE on endoscopy, interobserver variability, tissue fixation differences, and immunohistochemical staining differences (eg, antigen retrieval methods (25). Another important factor is the anatomical location from which the biopsy was taken, because biopsies obtained distal to the cardia have a significantly lower likelihood of showing a BE pattern.…”
Section: Discussionmentioning
confidence: 99%
“…These data support our hypothesis that the development of BE is a progression from CIM to BE, then to dysplasia. Further studies should be performed to determine whether the presence or absence of a BE pattern of CK7/CK20 immunostaining could predict progression to dysplasia or carcinoma, as previously suggested (25).…”
Section: Discussionmentioning
confidence: 99%
“…Some subsequent studies appeared to reproduce these findings (19,25,30,31) . However, other authors presented discordant results and they concluded that these patterns are not useful to differentiate BE from intestinal metaplasia of the cardia (6,7,13,20,21,27) . In spite of these inconsistencies, these studies produced some outcomes that deserve further consideration.…”
Section: Discussionmentioning
confidence: 88%
“…SHEARER et al (31) mentioned that similar patterns of CK7/CK20 expression were frequently observed in adjacent areas with and without goblet cells. MOHAMMED et al (21) identified the Barrett pattern in 55% of biopsies from inflamed or normal cardiac mucosa without evidence of intestinal metaplasia. GLICKMAN et al (13) noted that the immunophenotypes of the cardiac mucosa in patients with long-segment BE, shortsegment BE and normal esophagogastric junction were similar for Das-1 and CK7/CK20, but they were different from those of the gastric antral mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation